A COMPLETE SET OF SYSTEMS THINKING SKILLS. Issue 3 (6th October 2017) - Arnold, Ross D.; Wade, Jon P.
ABSTRACT: This paper proposes a complete set of systems thinking skills for use across many different disciplines. The paper places particular emphasis on the ability to assess each of the skills quantitatively, a comprehensible description of the skills, and the completeness of the set. The proposed skills derive from a review of the literature, the application of systems thinking experience, and the application of systems thinking to itself. Several different sets of systems thinking skills exist throughout the systems community, but common key concepts distill from these sets. When we consider combinations of these concepts separately, holistically, and together as a system, a single, cohesive set of skills emerges. Systems thinking is widely believed to be of critical importance across many different fields; some say that skillful use of systems thinking skills could have prevented such disasters as World War II, the Great Depression, and the Challenger space shuttle disaster, as well as lessened or avoided the effects of many major environmental disasters. At the opposite send of the spectrum, systems thinking can enhance health care, improve the economy, improve technology, laws, international and interpersonal relationships, schools, organizations, and so much more. However, this very useful skill set still lingers outside mainstream education. To address this problem requires a set of assessable, comprehensible systems thinking skills. This paper defines, describes, and details such skills.